Rapid Cycling Bipolar and Trauma-Related Personality Traits: Bridging the Gap Between Affective Dysregulation and Early-Life Adversity - Septina, Egy Atthahirah; Halimatus Sakdyah; Pramesta, Linda Ramadhanty; Muhammad Ikhsan; Alsa Shafira; Budi Cahyono; Hafid Algristian (Indonesian Scientific Publication, 2025)
Rapid cycling bipolar disorder (RCBD) represents a severe and treatment-resistant subtype of bipolar disorder in which patients experience at least four mood episodes within a year, often accompanied by greater psychiatric comorbidity, functional impairment, and suicide risk compared to non-rapid cycling cases. Childhood trauma and early-life adversity have been identified as critical contributors to emotional dysregulation, impulsivity, and treatment resistance, yet their role is frequently underrecognized in clinical practice. This case report describes a 30-year-old woman diagnosed with RCBD and a history of emotional and physical abuse in childhood, aiming to illustrate the complex interaction between trauma and affective instability while integrating neurobiological, psychological, and clinical perspectives. The patient underwent four weeks of inpatient evaluation that included structured interviews, collateral history from caregivers, psychometric assessments using the Young Mania Rating Scale (YMRS), Hamilton Depression Rating Scale (HAM-D), and Difficulties in Emotion Regulation Scale (DERS), as well as daily multidisciplinary observation. Over the past year, she experienced six distinct mood episodes with severe deficits in emotional clarity and impulse control, elevated DERS scores, and only partial response to pharmacological treatment with valproate and quetiapine. Clinical patterns and supporting literature suggest that trauma-induced dysregulation, involving amygdala hyperactivation and hypothalamic–pituitary–adrenal (HPA) axis disruption, played a central role. Improvement was achieved only after trauma-focused psychotherapy and psychosocial support were incorporated into her care. This case highlights the necessity of early trauma screening and integrative, trauma-informed management to improve diagnostic accuracy, treatment engagement, and long-term outcomes in complex bipolar presentations.